Dynamic characteristics of dwarf Chinese hickory trees under impact excitations for mechanical fruit harvesting - Xiaoqiang, Du; Chuanyu, Wu; Leiying, He; Junhua, Tong (International Journal of Agricultural and Biological Engineering, 2015)
Mechanical vibration is an effective fruit harvesting method. To evaluate the dynamic characteristics of dwarf Chinese hickory (Carya cathayensis Sarg.) trees and the influence of the tree structure on transmission and attenuation of dynamic response, a new method was proposed based on acceleration admittance measurement on dwarf Chinese hickory trees in orchard environment under impact excitation. The primary resonance frequencies of the tree can be determined based on the acceleration admittance measurement. The effect of the tree structure on the vibratory transmission was quantified using the attenuation ratio of the acceleration admittance. A 5-year-old dwarf Chinese hickory tree sample was tested. The responses at three resonance frequencies (5, 9 and 12 Hz) were analyzed because they were identified as the most effective bands of excitation for the main part of the tree specimen. The results reveal that the variation of the dynamic response along the testing tree is greatly related to the Chinese hickory tree structure. The attenuation ratio of the acceleration admittance at the branch crotches indicates the leader top crotch may amplify the acceleration admittance no matter what the crotch angle and the branch diameter is. Unlike the crotches, the branch chain nodes generally have negative influence on the acceleration admittance along the branch chains which heavily depend on the branch chain configuration. The branch chains with a chain angle no less than 150° and a wood diameter ratio close to 1.0 could produce little influence on the vibration transmission. For those branches with chain angle less than 150°, the vibration was generally attenuated at their chain nodes at three resonance frequencies. To impose impact excitations on the tree, high mechanical harvesting efficiency could be achieved on those branch chains which are almost straight and uniform. DOI: 10.3965/j.ijabe.20150801.003 Citation: Du X Q, Wu C Y, He L Y, Tong J H. Dynamic characteristics of dwarf Chinese hickory trees under impact excitations for mechanical fruit harvesting. Int J Agric & Biol Eng, 2015; 8(1): 17－25.